Effects of Strategic Leadership and External Environment on the Performance of Africa Inland Church Theological Training Institutions in Kenya - Munyao, Solomon Mbula (PAC University, 2021)
Performance is one of the biggest challenges facing organizations operating in the ever changing and complex 21st century business environment with strategic leadership playing a critical role in the achievement of organizational goals. The overarching objective of this study was to examine the effects of strategic leadership on the performance of AIC theological training institutions in Kenya with external environment as a moderating variable. The specific objectives were to determine the effects of strategic direction, organizational culture, organizational resource portfolio, strategic leadership and external environment on the performance of AIC theological training institutions in Kenya with the aim of creating new knowledge in this area of study. The study was anchored on strategic leadership theory. Experimental research design that adopted a mixed method approach was chosen. The target population was all the management members, employees and students in the 26 AIC theological training institutions in Kenya. A sample population of 219 management members, employees and third year students were selected from three AIC Bible Colleges using multistage purposeful two-state sampling technique. Open and closed ended questionnaires were administered to collect both quantitative and qualitative data which was then analysed using SPSS version 20. The results of the study indicated that organizational performance correlated with organizational culture, strategic leadership and organizational resource portfolio at (r=0.321, p<.001; r=0242, p<.001 and r=-0.145, p<.001). Its correlation with external environment was (r=-0.013, p<.001). The findings provide empirical strength to strategic leadership theory by supporting the assumption that strategic leadership increases an organization’s performance. Here, aspects related to managerial practice were rated low by respondents indicating the need for strategic leaders to make improvements in areas of physical and technological infrastructure in their organizations. Future studies could test the effects of the other aspects of strategic leadership on the performance of AIC theological training institutions in Kenya.
PhD Dissertation
Keywords: Strategic Leadership; External Environment Factors; Organizational Performance; Theological Training Institutions; African Inland Church; Organizational Culture